Teknologi dan Motivasi Belajar: Analisis Pengaruh Teknologi Informasi dalam Pembelajaran Pendidikan Agama Kristen - Pello, Eleonora Patricia Selfina (Perkumpulan Teolog Agama Kristen Indonesia, 2024)
This article explores the positive impact of information technology on student motivation in Christian Religious Education. The integration of digital platforms and innovative technologies has significantly enhanced the efficiency of the educational process, especially in the context of Christian Religious Education (CRE). The study reveals that the use of technology in learning, including interactive content and online learning tools, has sparked greater interest and enthusiasm among students to engage with and apply the Christian religious concepts taught. By utilizing qualitative descriptive research methods and focusing on library research, the study highlights the role of technology in enriching students' learning experiences, particularly in the current era of disruption. The findings emphasize that the effective use of technology positively influences student motivation, encouraging them to learn and explore Christian teachings with greater commitment. Contributions: This article explores the positive impact of information technology on student motivation in Christian Religious Education. It demonstrates how digital platforms and innovative technologies enhance student engagement and understanding of Christian teachings. The research contributes to the discussion on integrating technology into religious education, making it more interactive and efficient. Artikel ini membahas dampak positif teknologi informasi terhadap motivasi belajar siswa dalam Pendidikan Agama Kristen. Integrasi platform digital dan teknologi inovatif secara signifikan meningkatkan efisiensi proses pendidikan, khususnya dalam konteks Pendidikan Agama Kristen (PAK). Penelitian ini menunjukkan bahwa penggunaan teknologi dalam pembelajaran, termasuk konten interaktif dan alat pembelajaran daring, telah meningkatkan minat dan antusiasme siswa untuk terlibat dan menerapkan konsep-konsep agama Kristen yang diajarkan. Dengan menggunakan metode penelitian deskriptif kualitatif yang berfokus pada studi pustaka, penelitian ini menyoroti peran teknologi dalam memperkaya pengalaman belajar siswa, terutama di era disrupsi saat ini. Temuan penelitian menekankan bahwa penggunaan teknologi yang efektif dapat mempengaruhi motivasi belajar siswa secara positif, mendorong mereka untuk lebih berkomitmen dalam mempelajari ajaran Kristen. Kontribusi: Artikel ini mengkaji dampak positif teknologi informasi terhadap motivasi belajar dalam Pendidikan Agama Kristen. Teknologi digital dan platform inovatif meningkatkan keterlibatan siswa serta pemahaman ajaran Kristen. Penelitian ini berkontribusi pada pembahasan integrasi teknologi dalam pendidikan agama, menjadikannya lebih interaktif dan efisien.